Audit Committee Characteristics, Board Size, and Audit Report Lag: The Role of Ownership Concentration - Shanaya Alayka; Mazda Eko Sri Tjahjono; Muhammad Nawawi (MultiTech Publisher, 2026)
Timely audited financial statements are essential for market discipline, yet Indonesian property and real-estate firms still show substantial variation in audit completion time. Using ownership concentration as a moderator variable, this study investigates at how audit report lag is affected by the frequency of audit committee meetings, audit committee expertise, and board size. Property and real estate firms listed between 2020 and 2024 on the Indonesia Stock Exchange (IDX) are the subject of the study. Secondary data was gathered from audited annual financial statements and annual reports using a quantitative method. 305 observations from 61 businesses chosen by purposive sampling. Panel data regression and Moderated Regression Analysis (MRA) using EViews 12 were used to analyze the data. The results show that while audit committee expertise and board size have a significant positive impact on audit report lag, the number of audit committee meetings has a negative but insignificant effect. Additionally, the association between audit committee expertise and audit report lag, as well as the frequency of audit committee meetings, is strengthened by ownership concentration. On the other hand, the association between the size of the board size and audit report lag is weakened by ownership concentration. These results emphasize how crucial ownership concentration is in determining how well corporate governance systems work to increase audit timeliness.